PREVALENCE AND MANAGEMENT OF INFECTIONS IN HEMODIALYSIS PATIENTS: STRATEGIES FOR PREVENTION AND CONTROL - Muhammad Saqib Zafar; Aiman Tariq; Lailomah Yousaf; Waqar Mehmood; Syed Ahsan Ali Shah; Muhammad Ibrar; Faizan Banaras (Journal of Population Therapeutics and Clinical Pharmacology, 2024)
Background: Infections are a major complication for patients undergoing hemodialysis, contributing significantly to morbidity and mortality. Understanding the prevalence and effective management of infections in this population is crucial for improving patient outcomes and quality of care.Aim: This study aimed to investigate the prevalence of infections among hemodialysis patients presenting to the Nephrology Division at Khyber Teaching Hospital, Peshawar, from January 2023 to June 2023. The study also sought to evaluate the strategies for infection prevention and control.Methods: A cross-sectional analysis was conducted, involving a review of medical records of hemodialysis patients. Inclusion criteria encompassed hemodialysis patients with complete medical records within the specified timeframe, while exclusion criteria included patients with incomplete records or infections unrelated to dialysis. Data collection methods included systematic review and documentation of infection types and prevention strategies.Results: The study found that infections were prevalent in 45% of the hemodialysis patients. The most common infections were catheter-related bloodstream infections (CRBSIs), affecting 57% of the patients, followed by urinary tract infections (UTIs) at 12.5%, and respiratory infections at 10%. Implementing stringent infection control protocols, including regular hand hygiene, use of antimicrobial locks, and proper catheter care, significantly reduced infection rates. Specifically, CRBSIs saw a reduction rate of 61%, UTIs 48%, and respiratory infections 65%.Conclusion: The prevalence of infections among hemodialysis patients is a significant concern, with catheter-related bloodstream infections (CRBSIs) being the most common. Implementing robust infection prevention and control measures, including stringent hand hygiene, proper catheter care, and patient education, is crucial to mitigate infection risks and improve patient outcomes in this vulnerable population.